2013
DOI: 10.1155/2013/528724
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Tin Monosulphide Films Grown by Chemical Bath Deposition

Abstract: Tin monosulphide (SnS) films have been successfully grown by a simple and low-cost wet chemical process, chemical bath deposition (CBD), using tin chloride and thioacetamide as precursors and tartaric acid as complexing agent. The layers were grown on glass substrate at different bath temperatures (Tb) that varied in the range 50–70°C. The energy dispersive X-ray analysis (EDAX) studies showed that all the grown films were nearly stoichiometric. The X-ray diffraction analysis indicated that the films had an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…SnS has been investigated as co-catalyst to modify semiconductors for photocatalysis and hydrogen production. [7][8][9] Bi 2 S 3 is a narrow band gap (1.3-1.7 eV) n-type semiconductor with lamellar structure. Bi 2 S 3 has interesting characteristics such as strong light absorption capacity in the visible region and appropriate valence band (VB) and conduction band (CB) positions which make it an ideal material for hybridization with Al 2 O 3 for better directional charge migration in a heterostructure for water splitting and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SnS has been investigated as co-catalyst to modify semiconductors for photocatalysis and hydrogen production. [7][8][9] Bi 2 S 3 is a narrow band gap (1.3-1.7 eV) n-type semiconductor with lamellar structure. Bi 2 S 3 has interesting characteristics such as strong light absorption capacity in the visible region and appropriate valence band (VB) and conduction band (CB) positions which make it an ideal material for hybridization with Al 2 O 3 for better directional charge migration in a heterostructure for water splitting and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…SnS has been investigated as co-catalyst to modify semiconductors for photocatalysis and hydrogen production. 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Various sulfides of tin, lanthanum, cerium, cadmium, copper, and antimony are highly stable, straightforwardly synthesized, and have favorable band gap energies for tandem photovoltaics (PV). 8 12 Antimony sulfide, Sb 2 S 3 , in particular possesses an ideal 1.7 eV band gap to pair with silicon bottom absorbers and has been studied extensively. 13 Despite early results of open-circuit photovoltages of 770 mV from bath-deposited Sb 2 S 3 , 11 , 14 − 17 the intervening 25 years have seen little improvement.…”
Section: Introductionmentioning
confidence: 99%
“…For this SnS is very promising because of its high absorption coefficient (10 5 ), suitable bandgap for solar cells, and abundance in nature [5]. SnS thin films have been deposited by techniques such as electrodeposition [6], spray pyrolysis [7], sputtering [8], vacuum evaporation [9], and chemical-bath deposition (CBD) [10][11][12][13][14][15]. Despite the relatively low cost and simplicity of CBD, research reported on the formation of SnS thin films by CBD is insufficient and the topic needs further investigation.…”
Section: Introductionmentioning
confidence: 99%